Secondhand Smoke Increases the Risk of Psychiatric Morbidity: A Population-based Longitudinal Cohort Study - Jia-In Lee; Jiun-Hung Geng; Yi-Ching Lo; Ming-Been Lee; Szu-Chia Chen; Cheng-Sheng Chen (Asian Journal of Social Health and Behavior)
Introduction: Depression and anxiety are major global public health concerns associated with various negative outcomes. Secondhand smoke (SHS) exposure has been proposed as a potential risk factor. We aimed to investigate whether SHS exposure is associated with psychiatric morbidity in a large population-based cohort study. Methods: Data were derived from the Taiwan Biobank between December 2008 and December 2019, including over 120,000 noncancer participants aged 30–70 years. The cross-sectional analysis involved 88,510 never-smokers, while a longitudinal cohort of 19,575 participants with follow-up validated findings. SHS exposure was assessed through self-reported questionnaires, categorizing participants into exposure and nonexposure groups. Psychiatric morbidity was defined by either a self-reported history of diagnosed depression, a Patient Health Questionnaire 2-item (PHQ-2) score ≥3, or a Generalized Anxiety Disorder 2-item (GAD-2) score ≥3. Logistic regression adjusted for demographics and health factors analyzed the associations. Results: In the cross-sectional analysis, 8% reported SHS exposure, which was significantly associated with a higher prevalence of psychiatric morbidity (odds ratio [OR] = 1.26, 95% confidence interval [CI] = 1.12–1.42). Longitudinal analysis (mean follow-up: 47 months) supported these findings, with SHS exposure linked to an elevated risk of psychiatric morbidity (OR = 1.37, 95% CI = 1.07–1.74). Notably, SHS exposure ≥1 h/week nearly doubled the risk (OR = 1.97, 95% CI = 1.46–2.67). Conclusion: SHS exposure significantly increases the risk of psychiatric morbidity. Public health efforts are essential to reduce SHS exposure and address its mental health impacts.